RAHU Project: Assessing water security and climate change adaptation strategies in the glaciated Vilcanota-Urubamba river basin - Rau, Pedro (2020)
The Peruvian Andes are a hotspot of vulnerabilities to impacts in water resources due to the propensity for water stress, the highly unpredictable weather, the sensitivity of glaciers, and the socio-economic vulnerability of its population. In this context, we selected the Vilcanota-Urubamba catchment in Southern Peru for addressing these challenges aiming at our objectives within a particular hydrological high-mountain context in the tropical Andes: a) Develop a fully-distributed, physically-based glacier surface energy balance model that allows for a realistic representation of glacier dynamics in glacier melt projections; b) Design and implement a glacio-hydrological monitoring and data collection approach to quantify non-glacial contributions to water resources and the impact of catchments interventions; c) Mapping of human water use at high spatiotemporal resolution and determining current and future levels of water (in)security; and d) Integrate last objectives in a glacier - water security assessment model and evaluate the tool's capacity to support locally embedded climate change adaptation strategies.